FRI0361 The use of leflunomide in a paediatric rheumatology clinic. (23rd January 2014) - Keidel, S.; Wilkinson, N.
Abstract : Background: Methotrexate (MTX) is the anchor drug used in the treatment of juvenile idiopathic arthritis (JIA). Leflunomide (LFD) has comparable efficacy to MTX in adults with rheumatoid arthritis, and there is evidence of efficacy in polyarticular JIA 1, 2 .Combination therapy with MTX is low risk in adults 3 but there is little data in the paediatric population 2 . Objectives: To examine the cohort of JIA patients treated with LFD in our tertiary paediatric rheumatology centre, to determine safety, tolerability, and efficacy of this drug in routine practice. Methods: 30 JIA patients on LFD were identified by computerised search of the local paediatric rheumatology database. Case notes were reviewed retrospectively. Our practice is to dose LFD by weight, 20mg daily (>40kg), 10mg (10-40kg), and 5mg (<10kg), and to monitor as per BSR guidelines. Demographics, diagnosis, treatment indication, DMARD history, and adverse events were recorded. Outcome was divided into LFD responders (ACR 50 response or greater), non-responders, and partial responders (non-sustained response or need for treatment escalation). Results: The combined treatment duration was 47 patient-years. The median age at LFD initiation was 12y (range 3-19y) and median disease duration 4.5y (0-10y). 90% were female, 56% had polyarticular disease, and 26% had uveitis. Previous therapy included MTX in 96% patients and biologics in 21%. The reasons for LFD commencement were: MTX inefficacy 19 patients (63%), MTX intolerance 12 patients (40%), and 13% for other reasons. 67% patients were on LFD 20mg daily and 63% were on combination therapy (39% MTX, 36% biologics, 14% other). The mean dose of MTX co-therapy was 18.5mg weekly. Tolerability and safety: LFD was continued for a median of 15mo (2-58mo); 64% remained on treatment. Side effects were reported in 8 patients (27%), of whom half were on combination therapy with MTX, and 5 required LFD cessation. Of the 11 patients switched to LFD due to MTX intolerance, 73% tolerated LFD well. Two patients developed neutropaenia; one of whom, on LFD monotherapy, required drug withdrawal for a serious adverse event (SAE). There were no other SAE and no drug-related instances of transaminitis or hypertension. Efficacy: Of the patients who tolerated LFD, 42% were responders, 25% partial responders, and 21% non-responders. All of the 4 patients with oligoarticular JIA responded well to treatment. All of 3 patients with active uveitis prior to LFD commencement required treatment escalation for eye disease. Conclusions: LFD was well-tolerated with a comparable safety profile to MTX. There was one case of neutropaenic sepsis not detected by routine monitoring over a 47 patient-year follow up. There was no excess of adverse events or intolerance in the cohort on combination therapy with LFD and high dose MTX. LFD is an effective treatment in MTX-failed and MTX-intolerant chronic JIA patients with a similar efficacy profile to other reports 2, 3 . LFD was ineffective when specifically used for uveitis in a small group of patients. References: Silverman E et al. N Engl J Med. 2005;352:1655. Foeldvari I, Wierk A. J Rheumatol 2010;37:1763-7. Lee S et al. Scand J Rheumatol 2009;38:11–14. Disclosure of Interest: None Declared